Evaluación del manejo de suelos contaminados por actividad minera en el sur del departamento de Córdoba y el Bajo Cauca Antioqueño (2021)
In the south of the department of Córdoba, as in the lower Cauca Antioqueño, gold mining processes are presented in an artisanal and traditional way without there being an assessment and management of the environmental impacts associated with said activity. Natural resources such as air, water and soil are directly and indirectly affected due to unsustainable mining practices. Soil recovery processes must be based on sustainable and environmentally friendly studies, the use of native plant species to contribute to soil formation processes. For the evaluation of the management of soils contaminated by mining activity, three field stations were carried out: the first station was carried out on a farm via Caucasia-Jardín, the second broken station and rubber cultivation in the San José de Uré municipality and the third station. It was on the Mina el Alacrán road. In the different study stations carried out in Córdoba and Bajo Cauca Antioqueño, soil profiles were observed, some being degraded by gold mining, making it necessary to change unsustainable practices, the implementation of environmentally friendly technologies, demarcation and signaling of the areas and the implementation of safety and health at work for miners, to the extent that environmental epidemiological programs are implemented to assess the population affected by mining.